IMPLIKASI HUKUM PENGECEKAN SERTIFIKAT TANAH SECARA ONLINE - Sundaru Guntur Wibowo; Fredy Susanto; Ardila Prihadyatama; Naufal Ahmad. A (LPPM Universitas Sains dan Teknologi Komputer, 2023)
PPAT's responsibility for discrepancies in electronic certificate checking results and efforts to resolve discrepancies in electronic certificate checking results. This writing uses normative legal research methods by examining regulations related to the role of PPAT in checking certificates electronically in land sale and purchase agreements, by applying a statutory approach, and a conceptual approach, as well as using primary, secondary and legal materials. tertiary then the results are described descriptively. The research results show that the responsibility of PPAT, which is directly involved in the electronic certificate checking process, is to ensure that the data, both jurisdic data and physical data on the results of electronic certificate checking, are in accordance with the original certificate. Efforts that can be made by PPAT if there is a data discrepancy, PPAT sends a notification through the relevant information service system so that data that is inconsistent is immediately updated or by visiting the BPN office, bringing proof of the results of checking the printed electronic certificate and the original certificate. Then the BPN will provide information by updating the data in the system.